PENGARUH TUNJANGAN SERTIFIKASI TERHADAP KINERJA GURU SMP NEGERI SEKECAMATAN MEUREUBO KABUPATEN ACEH BARAT - Damrus Damrus (universitas teuku umar, 2017)
ABSTRACT Teachers’ performance determines the quality of educational system. Education will be qualified when teachers are referred to the organized vision, mission, purpose, and goal in order to respond to various changes by generating all potential resources in educational institution. Teachers’ work satisfaction is one of the important aspects which have to be heeded by management in order to increase teachers’ quality of performance. When work satisfaction is fulfilled, teachers will tend to have high morale in doing their job. The research used descriptive explanatory quantitative method which was aimed to measure the correlation between two or more variables. The data were gathered by conducting interviews, questionnaires, and documentary study. The population was 39 teachers as the government employees at all public junior high schools in Meureubo Subdistrict who had received certification allowance, and all of them were used as the samples, taken by using census sampling technique. The gathered data were analyzed by using interval scale, and multiple regression. The result of the research showed that certification allowance had positive and significant influence on teachers’ performance. Keywords: Certification Allowance, Teachers’ Performance